Phytogenic Feed Additive Enhance Innate and Humoral Immune Response to Newcastle Disease Virus Vaccination in Broiler Chickens - Aly, Shereen M.; Hafez, Abeer S.; Nada, Abdel Fatah A.; Hussein , Hussein A. (International Journal of Poultry Science, 2019)
Objective: The objective of this study was to evaluate the effects of a phytogenic feed additive (Biostrong 510), which contains Saponins to modulate the immune system of poultry and to improve vaccination efficacy. Materials and Methods: In this study, four groups of broiler chickens (40 each) were reared for 10 days under same conditions. Groups 1 and 2 were fed diets containing phytogenic feed additives (PFA) at 150 mg kg–1 (Biostrong 510, Delacon Biotechnik GmbH, Austria) whereas groups 3 and 4 continued to be fed without any PFA as control groups. Chickens in groups 1 and 3 were vaccinated with Newcastle disease vaccine (NDV-Lasota strain) at 14 days of age whereas groups 2 and 4 were left unvaccinated as controls. Immune organ/body weight ratio; phagocytic activity; nitric oxide, lysozyme and total antioxidant activity were measured. In addition, mean titers of heamagglutinating antibodies to NDV were determined. Results: This study showed that in comparison to the control groups, chickens fed Biostrong 510 demonstrated a significant increase in bursa/body weight ratio, significant increase in total antioxidant activity and phagocytic indexes. However, no significant effects were determined in nitric oxide and lysozyme concentration. Conclusion: Biostrong 510 has the potential to stimulate the innate immune response and enhance antibody production against NDV.